Socio-Pragmatic Approach to Teenagers’ Conversational Strategies - Ortega Salamanca, Francisco José; Vargas Cortés, Belcy Victoria (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents the results of a research project supported in socio-pragmatic theoretical references, such as politeness and rudeness. Its main purpose was to identify the most common conversational strategies between tenth graders from educational institutions of Nobsa and Cómbita (Boyacá, Colombia), in order to interpret some of the comradeship strategies used by these students in their day-to-day conversations. A qualitative approach based on Conversational Analysis was implemented, coming from the field of Speech Ethnography. The research process was built upon three fundamental bases: the diagnosis, information gathering and implementation of instruments phase, and the phase of analysis and interpretation of the obtained data. The outcome revealed some of the most popular conversational strategies and treatment formulas used by the teenagers in informal contexts, which help them to establish a certain degree of fellowship amongst themselves.